PELATIHAN PEMULASARAAN JENAZAH PEREMPUAN SEBAGAI STRATEGI PEMBERDAYAAN PEREMPUAN DI DESA KARANGMOJO MAGETAN - Binsa, Abdul Aziz; Rohman, Muhammad Abdur; Meilana, Putri Bibit; Mushtofa, Syahrul; Dzikriyya F. B., Ihda Zullaida; Wahyudi, Oky Bagus; Chandra W., Rengga Krishna; Wahidah, Anti Syahrotul; Ngabdulloh, Moh Riza; Khunaifa, Naimul; Nurfajria, Rena; Hidayatulloh, Ahmad Aris; Awalia, Nila Hani; Awandar, Tia Anhar Setio (LP2M Institut Agama Islam Ngawi, 2025)
Corpse care (pemulasaraan jenazah) is a collective obligation (fardhu kifayah) in Islam, encompassing bathing, shrouding, praying, and burying the deceased. However, in community practice, this duty is often entirely delegated to male funeral attendants (modin), even for female corpses, limiting community participation and understanding, especially among women. This community service project aimed to empower women by training them on the procedures for female corpse care in accordance with Islamic law. The implementation method consisted of four stages: (1) preparation, (2) execution (theoretical material delivery and direct practice), (3) mentoring, and (4) evaluation. The participants were 35 mothers from the Family Welfare Empowerment (PKK) group in Karangmojo Village. The results showed high enthusiasm and participation from the attendees, reaching 90% of the target. Participants gained not only a comprehensive theoretical understanding of the laws and procedures of the